Synthesis and investigation on microstructural, mechanical features of mesoporous hardystonite/reduced graphene oxide nanocomposite for medical applications - Bagherpour, Iman; Yaghtin, Amirhossein; Naghib, Seyed Morteza; Molaabasi, Fatemeh (Frontiers in Bioengineering and Biotechnology, 2023)
The use of hardystonite (Ca2ZnSi2O7, HT)-based composites could be one the main strategies to improve mechanical properties closing to natural bone. However, there are a few reports in this regard. Recent findings indicate that graphene is a promising biocompatible additive in ceramic-based composite. Here, we propose a simple approach for the synthesis of porous nano- and microstructured hardystonite/reduced graphene oxide (HT/RGO) composite using a sol-gel method followed by ultrasonic and hydrothermal processes. Integrating GO to the pure HT increased the bending strength and toughness values about 27.59% and 34.33%, respectively. It also allowed the increment of compressive strength and compressive modulus by about 8.18% and 86%, respectively, and improvement in the fracture toughness about 11.8 times compared to pure HT. The formation of HT/RGO nanocomposites with different RGO weight percentages ranging from 0 to 5.0 has been investigated by scanning electron microscopy (SEM) and X-ray diffraction and the efficient incorporation of GO nanosheets into HT nanocomposite as well as the mesoporous structural properties were also confirmed by Raman, FTIR and BET analyses. The cell viability of HT/RGO composite scaffolds was assayed by methyl thiazole tetrazolium (MTT) test in vitro. In this regard, the alkaline phosphatase (ALP) activity and the proliferation rate of mouse osteoblastic cells (MC3T3-E1) on the HT/1 wt. % RGO composite scaffold enhanced in comparison with the pure HT ceramic. The adhesion of osteoblastic cells on the 1% wt. HT/RGO scaffold was interesting as well. In addition, the effect of 1% wt. HT/RGO extract on the proliferation of osteoblast human G-292 cells was successfully evaluated and remarkable observations were obtained. All together it can be said that the proposed bioceramic hardystonite/reduced graphene oxide composites can be a promising candidate for designing hard tissue implants.